Effects of liming on the fine root production, fine root morphology and ectomycorrhizal association in a chestnut orchard - FURUSAWA, Hitomi; NOGUCHI, Kyotaro; NAKANO, Shota; YAMANAKA, Takashi; KINOSHITA, Akihiko; MIZUTANI, Kazuto; TANAKA-ODA, Ayumi; OBASE, Keisuke; SHIBATA, Hisashi (Root Research, 2022)
In general, soils in Japan tend to be acidified by base cation leaching due to much amounts of precipitation. Liming is often conducted to reduce soil acidity, and therefore favorable for cultivations of crops, vegetables, and fruit productions. Fine roots and mycorrhizal fungi are mainly distributed in surface soils and are likely susceptible to pH changes caused by liming, although there is still limited information on them. In this study, we examined effects of liming on fine root growth, fine root morphology and formation of ectomycorrhiza in a chestnut (Castanea crenata) orchard in Yamanashi Prefecture, Japan, using an ingrowth core method. We set up liming- (40 kg CaO ha–1) and control-plots in May and July 2016. Ingrowth cores were installed when the liming was conducted (May or July) and were collected in October 2016. Fine root growth rates were larger in the liming- than in control-plots set in May, while they were not significantly different between the treatments conducted in July. The very fine root ratio (VFRR), an index of fine root morphology, was larger in plots set in May than in those set in July, whereas the effect of liming on the VFRR was not significant. On the other hand, the ratio of mycorrhizal root tips to total root tips was not significantly different in all plots (approx. 40-60% of root tips). These results suggest that liming conducted in spring can promote fine root growth, without decreasing the rate of ectomycorrhizal formation in this chestnut orchard.